A New Methodology for Laboratory Evaluation of Neurosurgical Approaches Based on the Volume and Shape of the Surgical Space with a Mathematical Model to Quantify the Surgical Maneuverability in Laboratory Settings - Salma, Asem; Alkandari, Abdulrahman; Sammet, Steffen; Ammirati, Mario (Journal of Neurological Surgery Part B: Skull Base, 2012)
We conducted this study to validate the volume/shape of the surgical exposure and to introduce a mathematical model to quantify the maneuverability in a surgical space. We executed the pterional and lateral supraorbital approach four times in fresh cadavers in skull base laboratory. The surgical volumes were filled with a computed tomography (CT)-imageable mixture; CT scans were obtained to evaluate the volume and shape of the surgical space. The volume of the surgical space was 23.60 and 32.90 mL for the lateral supraorbital and pterional approach, respectively, (p < 0.05). The three-dimensional shape of the lateral supraorbital approach was cylindrical and that of the pterional approach pyramidal. The volume of the surgical approach can be used to define, together with other variables, the maneuverability (maneuvering in a surgical volume) by using the following formula where M, A, V, and L represent the maneuverability, the degree of the surgical freedom, the volume of the surgical exposure, and the surgical depth, respectively. Volume and shape of the surgical exposure are two objective parameters that can be used to define and contrast different microsurgical approaches in a laboratory setting. The volume of the surgical exposure may be integrated into a mathematical formula defining maneuverability.
Keywords: anatomical study; cadaveric study; neurosurgical approach; surgical operability